2011
DOI: 10.1111/j.1744-6171.2010.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Screen for Child Anxiety Related Emotional Disorders in a Rural High School Population

Abstract: The SCARED was found to be a reliable tool in the rural adolescent population. Differences in some factors suggest further research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This score was higher as compared to the mean scores of the 41-item version of the SCARED in community samples described by North American youth studies (19.36, 21.24, 18.12, and 21.50, respectively;Boyd et al, 2003;Haley et al, 2011;Wren et al, 2004;Wren et al, 2007), German youth studies (18.85;Essau et al, 2002), Belgium youth studies (16.10; Muris, Merckelbach, et al, 2002), as well as Chinese youth studies (14.99;Su et al, 2008). However, the scores of the SCARED for Brazilian children and adolescents were comparable to the results found in studies with Spanish youth (24.31;Vigil-Colet et al, 2009), Italian Youth studies (22.60;Ogliari et al, 2006) and lower than studies with South African youth (31.89 and 33.00, respectively; Muris, Schmidt, et al, 2002;Muris et al, 2006).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…This score was higher as compared to the mean scores of the 41-item version of the SCARED in community samples described by North American youth studies (19.36, 21.24, 18.12, and 21.50, respectively;Boyd et al, 2003;Haley et al, 2011;Wren et al, 2004;Wren et al, 2007), German youth studies (18.85;Essau et al, 2002), Belgium youth studies (16.10; Muris, Merckelbach, et al, 2002), as well as Chinese youth studies (14.99;Su et al, 2008). However, the scores of the SCARED for Brazilian children and adolescents were comparable to the results found in studies with Spanish youth (24.31;Vigil-Colet et al, 2009), Italian Youth studies (22.60;Ogliari et al, 2006) and lower than studies with South African youth (31.89 and 33.00, respectively; Muris, Schmidt, et al, 2002;Muris et al, 2006).…”
Section: Discussionmentioning
confidence: 67%
“…Meanwhile, data had demonstrated that the SCARED presented good internal consistency as well as good test-retest reliability (Birmaher et al, 1997(Birmaher et al, , 1999Boyd et al, 2003;Essau et al, 2002;Haley et al, 2011;Muris, Merckelbach, van Brakel, et al, 1999;Su et al, 2008), parent-child correlation (Birmaher et al, 1997;Muris, Merckelbach, van Brakel, et al, 1999;Su et al, 2008;Wren et al, 2004), convergent validity (Boyd et al, 2003;Essau et al, 2002;Muris et al, 1998;Muris, Merckelbach, et al, 2002;Monga et al, 1998;Su et al, 2008) and discriminant validity (Birmaher et al, 1997(Birmaher et al, , 1999Monga et al, 1998;Su et al, 2008). In general, these studies have suggested that the SCARED is a reliable and valid screening instrument to rate anxiety symptoms in children and adolescents.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the psychometric characteristics of the SCARED have been well established, 5,19,20,[24][25][26] This scale is used extensively in research and has good evidence of both reliability and validity. 29 Its reliability coefficient is high (α = 0.81).…”
Section: Diagnostic and Statistical Manual Of Mental Disordersmentioning
confidence: 99%
“…Psychometric studies support good internal consistency, testretest reliability, and discriminant validity [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 87%